2013
DOI: 10.21149/spm.v55i6.7301
|View full text |Cite
|
Sign up to set email alerts
|

Sweetened beverages intake, hyperuricemia and metabolic syndrome. The Mexico City Diabetes Study

Abstract: Objective. To determine prevalence of hyperuricemia and its relation with intake of sweetened beverages (SB) and metabolic syndrome (MS) in low income urban Mexican population. aterials and methods. A cross-sectional analysis of The Mexico City Diabetes Study, a prospective population-based investigation (1 173 participants) was performed. We used logistic egression, adjusted by pertinent variables. We determined prevalence of hyperuricemia and explored associations of uric acid levels with MS and intake of SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…This study examined the risk factors for hyperuricemia in a cohort with a high proportion of obesity and metabolic syndrome and in two obesity case-control studies. The prevalence of hyperuricemia in these groups was similar to other studies with metabolically compromised subjects [5,39,40,41]. A previous study of hypertensive Europeans reported a lower prevalence of hyperuricemia (17%) [5], in contrast with our results and those of another study in a European population that also observed a higher prevalence of hyperuricemia (29% and 25%, respectively) [40].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study examined the risk factors for hyperuricemia in a cohort with a high proportion of obesity and metabolic syndrome and in two obesity case-control studies. The prevalence of hyperuricemia in these groups was similar to other studies with metabolically compromised subjects [5,39,40,41]. A previous study of hypertensive Europeans reported a lower prevalence of hyperuricemia (17%) [5], in contrast with our results and those of another study in a European population that also observed a higher prevalence of hyperuricemia (29% and 25%, respectively) [40].…”
Section: Discussionsupporting
confidence: 88%
“…The results in our study have the same direction as previous reports; however, a larger effect was observed in children and adult women from the case-control study. Additionally, the well-known association between hyperuricemia and metabolic syndrome was also observed [39,45,46,47,48] in this study, particularly among girls and adult women from the case-control study. However, it is important to note that these women are younger and have a different menopausal status, compared to the older female participants from the HWCS.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As is known dyslipidemia was the basic of VAI increase. One Mexican population study revealed that sweetened beverages intake increased the risk of hyperuricemia and obesity [ 34 ]. Maybe keep fit and diet control was helpful for visceral obesity, specially in Chinese males, since Chinese individuals had the most deleterious abdominal visceral fat distribution and accumulation other than Europeans at a given BMI or WC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 7/10 adult Mexicans were overweight or obese, 3/10 were hypertensive, and 1/10 were diabetic [3][4][5] . In addition, the Mexico City Diabetes Study, a prospective population-based cohort that included 1,173 participants, reported a prevalence of 26.5 and 19.5% for asymptomatic hyperuricemia in men and women, respectively 6 . Furthermore, this condition was an undiagnosed characteristic in the majority of these individuals.…”
Section: Introductionmentioning
confidence: 99%